2014
DOI: 10.1182/blood-2013-11-536433
|View full text |Cite
|
Sign up to set email alerts
|

Determining cell-of-origin subtypes of diffuse large B-cell lymphoma using gene expression in formalin-fixed paraffin-embedded tissue

Abstract: Key Points A 20-gene gene expression-based assay accurately and robustly assigns COO subtypes of DLBCL using formalin-fixed paraffin-embedded tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
505
5
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 549 publications
(534 citation statements)
references
References 21 publications
19
505
5
5
Order By: Relevance
“…Ennek az az oka, hogy az algoritmus nem tudja 100%-os biztonsággal elkülöníteni a csoportokat, de még az R-CHOP protokollt használva is egyértelműen segít a prognózis becslésében [4]. Scott és mtsai 2014-ben közölték, hogy a Lymph2CX GEP-módszert biztonsággal lehet alkalmazni formalinfixált szöveteken, és így biztonsággal el lehet különíteni az ABC és GCB típust [5]. Később egy új prognosztikai modellt is javasolnak, amely a fentiek mellett figyelembe veszi a nemzetközi prognosztikai indexet (IPI) és a bcl-2/myc expressziót [6].…”
Section: öSszefoglaló Közleményunclassified
“…Ennek az az oka, hogy az algoritmus nem tudja 100%-os biztonsággal elkülöníteni a csoportokat, de még az R-CHOP protokollt használva is egyértelműen segít a prognózis becslésében [4]. Scott és mtsai 2014-ben közölték, hogy a Lymph2CX GEP-módszert biztonsággal lehet alkalmazni formalinfixált szöveteken, és így biztonsággal el lehet különíteni az ABC és GCB típust [5]. Később egy új prognosztikai modellt is javasolnak, amely a fentiek mellett figyelembe veszi a nemzetközi prognosztikai indexet (IPI) és a bcl-2/myc expressziót [6].…”
Section: öSszefoglaló Közleményunclassified
“…These findings are very similar to those found in previous studies irrespective of the nature (fresh frozen or FFPE) of DLBCL specimens investigated. 10,13,14,21 In general, the samples showing discrepant classes by different classifiers had a low confidence score for either ABC or GCB class assignment. 13 It is possible that these cases are in a 'molecular grey zone' , and their class cannot be accurately defined, no matter which classifiers used.…”
Section: Dlbcl Coo Classification By Qrt-pcr With Fluidigm Dynamic Arraymentioning
confidence: 99%
“…[6][7][8][9] Several studies have investigated the possibility of COOclassification of DLBCL using FFPE tissues by quantitative measurement of mRNA expression, including quantitative nuclease protection assay, 10 (GEP) with the Affymetrix HG U133 Plus 2.0 platform or the Illumina whole-genome DASL assay, [11][12][13] and NanoString technology. 14 In general, these studies demonstrated high confidence of COO-classification of DLBCL using FFPE tissues and a robust separation in overall survival between ABC and GCB-DLBCL.…”
mentioning
confidence: 99%
“…First, data from Vancouver suggest MYC and BCL2 protein dual expressers (DEs) are at increased risk of CNS relapse. Savage et al examined the correlation between DE status, cell of origin (COO; Lymph2Cx nanostring 57 and Hans algorithm), and CNS relapse in 428 patients with de novo DLBCL treated with R-CHOP (largely without CNS prophylaxis).…”
Section: Casementioning
confidence: 99%